Specific TCR V–J gene segment recombinations leading to the identification pan-V–J CDR3s associated with survival distinctions: diffuse large B-cell lymphoma. Issue 6 (12th May 2022) - Cios, Konrad J.; Huda, Taha I.; Eakins, Rachel A.; Mihyu, Moody M.; Blanck, George
Abstract: In the diffuse large B-cell lymphoma (DLBCL) setting, we examined lymph node biopsy, T-cell receptor features, and the DLBLC patient human leukocyte antigen (HLA) alleles, to provide a basis for assessing survival distinctions represented by the National Cancer Institute Center for Cancer Research (NCICCR) dataset. While previous analyses of other cancer datasets have indicated that specific T-cell receptor (TCR) V or J gene segments, independently, can be associated with a survival distinction, we have here identified V–J recombinations, representing specific V and J gene segments associated with survival distinctions. As specific V–J recombinations represent relatively conserved complementarity determining region-3 (CDR3) amino acid sequences, we assessed the entire DLBCL NCICCR dataset for such conserved CDR3 features. Overall, this approach indicated the opportunity of identifying DLBCL patient subpopulations with TCR CDR3 features, and HLA alleles, with significant survival distinctions, possibly identifying cohorts more likely to benefit from a given immunotherapy.